(untitled) (Research, Society and Development, 2021)
Objectives: The aim of this study was to reflect and review about oral health promotion in the context of the primary school environment, describing health promotion methods in primary education and health promotion incentive programs in primary education. Literature review: Conducting the oral health assessment carried out in the school environment requires, initially, the recognition of abilities related to the health team itself, as well as to education professionals, who represent a good part of the structure of the school. Currently, the commitment of the dental profession is mainly focused on the prevention of oral diseases, which represents a much simpler mechanism, with less cost and wiser healthcare. From this perspective, the need for teaching and motivating children in oral hygiene habits is highlighted, considering that the methods of education and motivation are intended to clarify individuals about oral diseases as well as to change their hygiene habits. Final considerations: The school has the role of a favorable social and educational environment when it comes to working knowledge and changes in behavior. From this perspective, understanding the needs of children in primary education is of fundamental importance for health and education professionals to commit themselves, in order to positively influence this population and act together with them as health multipliers.